2020
DOI: 10.3389/feart.2020.571310
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Method Approach for Quantification of In- and Exfiltration Rates from the Subterranean Estuary of a High Energy Beach

Abstract: Accurate SGD (submarine groundwater discharge) mass export calculations require detailed knowledge of the spatial and temporal variability in SGD rates. In coastal aquifers, SGD includes a terrestrial freshwater component as well as a saline component originating from circulating seawater. Representative field measurements of SGD rates are difficult to conduct, because SGD is often patchy, diffuse, and temporally variable, especially under tidal influence and high wave activity. In this study, a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…This distribution is presumably related to observable changes within geochemical conditions along the flow path of the intertidal recirculation cell, most likely caused by different sources and residence times of porewater [ 19 , 51 , 52 , 53 ]. The degradation state and composition of DOM which influence the presence of cluster II and III at Spiekeroog beach are in turn influenced by the mixing of the terrestrial and marine endmembers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distribution is presumably related to observable changes within geochemical conditions along the flow path of the intertidal recirculation cell, most likely caused by different sources and residence times of porewater [ 19 , 51 , 52 , 53 ]. The degradation state and composition of DOM which influence the presence of cluster II and III at Spiekeroog beach are in turn influenced by the mixing of the terrestrial and marine endmembers.…”
Section: Discussionmentioning
confidence: 99%
“…Porewater samples that are linked to cluster III were characterized by the highest ammonium, silicate, dissolved iron, and FDOM concentrations, which is in line with their link to the lower beach (ridge, LWL). This can especially be explained by the LWL being an exfiltration area of the subterranean estuary fed by recirculating seawater and fresh groundwater from the island’s freshwater lens [ 51 , 53 ]. On average, the DOM compounds associated with cluster III had the lowest degradation index and DBE but highest ITerr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a typical hydrological zonation with an upper saline plume, a freshwater discharge tube, and a saltwater wedge (Beck et al, 2017), whereby the ridge acts as an additional infiltration zone inducing the existence of two, at least temporally occurring, saltwater recirculation cells (Grünenbaum et al, 2020a). With a multi-method approach, Grünenbaum et al (2020b) quantified in-and exfiltration rates in the intertidal zone and showed that infiltration occurs above mean sea level while net exfiltration occurs below, with exchange rates clearly depending on beach topography. With a transient variable density groundwater flow and transport model Greskowiak and Massmann (2021) demonstrate how transient beach morphology and regular storm floods affect subsurface flow and transport pattern (Figure 7).…”
Section: Sandy Beach System and Biogeochemical Observationsmentioning
confidence: 99%
“…Also, it was done to allow to introducing the effect of dynamic morphology without the need for a step-wise/transient re-gridding of the model domain (see below). Note that the vertical hydraulic gradients in the system are very small compared to the lateral gradients such that the unresolved vertical gradients within the up to 3 m thick saturated zone in the first layer have not much effect on the overall groundwater flow behaviour in the deeper zones.The model accounts for the topography variation over time, loosely based on linear interpolation of available topography scans fromGrünenbaum et al (2020b). A transient Cauchy-Boundary ( ┌ S ) in the intertidal zone(Figure 1 top)reflects the tide-averaged hydraulic heads depending on a time-varying morphology(Figure 1, bottom).…”
mentioning
confidence: 99%